Dealer-supplier relationship satisfaction: Antecedent factors and its impact on trust and commitment - Perumal, Selvan; Mohd Noor, Nor Azila; Othman, Abdul Rahim; Adam, Mohamad Zainol Abidin; Ramachandram, Rajoo (Universiti Utara Malaysia, 2012)
Relationship satisfaction is an important factor in understanding the development, enhancing, and maintaining of buyer-seller relationships in inter-organizational contexts.This study investigated the influence of antecedent and consequences of dealers’ relationship satisfaction in the context of supplier-dealer relationship in Malaysian automobile industry.This study explores the influences of use of power by supplier on dealers’ relationship satisfaction.This study also examined the relationship between dealers’ relationship satisfaction and its consequences, namely trust and commitment.Hypothesized relationships are tested using survey responses from a sample of 107 new car dealers.The study founds that only non-coercive power has significant relationship with dealers’ relationship satisfaction.Consequently, the study also indicated that dealers’ relationship satisfaction is positively related with their trust and commitment.Results are compared with earlier findings and implications for future research are discussed.